Peru: struggle for multicultural integration and the danger of modernity in education (Revista Estudios Psicológicos, 2021)
The present research aims to reflect on what to do in the educational community in general. This is to integrate all students in their own and broad pedagogical policy, listening to each community's voices, and of course, their problems. For this, a brief historical tour was made, revealing the main educational policies from the founding of the Republic to the present, highlighting the desire of successive governments to implement foreign pedagogical models in their erroneous attempt to "modernize" the nation. Likewise, it was analyzed how this modernization process does not provide real solutions to the Peruvian pedagogical universe in the current neoliberal context. On the contrary, it is exclusive and outside the national context, where we must identify ourselves as a multicultural country, with different languages, customs, stories, traditions, etc.
Keywords: History of education; indigenous education; multiculturalism; modernity; educational integration